Coordenadores/as pedagógico/a e o direito à educação: concepções e modos de ação - Brandão, Lucelia Caroline Ferreira (2023)
This research is linked to the Teaching-Learning Process Line (PEA) of the Graduate Program in Education (PPGE) of the Federal University of Paraíba (UFPB) and aims to understand the conceptions and modes of action of the Coordinators/ the Pedagógicos/as - CoPs, as mediators of learning and the guarantee of the right to education in municipal public schools of Basic Education in the municipality of Codó. The CoP performs two main functions with the teachers at school: to create and mobilize spaces and training devices, in accordance with the educational purposes that are present in the Political-Pedagogical Project of the school; and articulate the collective work in the institution, considering the participation of the school community. This work is characterized as a qualitative field research, anchored in assumptions of Historicaldialectical Materialism, considering, with regard to the educational field, the totality and historicity of phenomena and subjects, from the understanding of all their mediations and correlations with the investigated object. The instruments used for data collection were participant observation, semi-structured interviews and a questionnaire applied to three CoPs working in different public schools in the Early Years located in the urban area of the municipality of Codó, in the state of Maranhão. Data analysis was performed based on Bardin's Categorical Content Analysis (2016) from the following categories: CoP Functions and Modes of Action; Conceptions of the CoPs around the right to education; and Formation of the professional identity of the CoPs. The data presented revealed that the functions and modes of action of the Pedagogical Coordinators/the research participants, many times, are still more centralized in the supervision of the students' learning than in the active and participative monitoring of the actions elaborated with/for the teachers. With regard to the conceptions of the CoPs around the right to education, the data indicated that, one of the main didactic strategies employed by the teachers, with the endorsement of the CoPs, to ensure the guarantee of the right to education still restricts students' participation and performance in large-scale assessments.